Total Organic Carbon (TOC) Value Prediction in Source Rock Potential at North East Java Basin, Indonesia - Paulus Leonardo Manurung; Rahmat Catur Wibowo; Ordas Dewanto (UIR PRESS, 2021)
This research aims to determine the potential of the source rock in the Kujung and Cepu Formations in the North East Java Basin, using Total Organic Carbon (TOC). TOC is calculated using the Passey method. The Passey method is used by overlaying the sonic log and the resistivity log and determining the baseline to get the separation of Δlog resistivity, which is then used to predict the TOC log by including the LOM (Level of Organic Maturity) variable obtained from the data of vitrinite reflectance. After the TOC log value is obtained, a correlation is made with the TOC core value. The prediction result of TOC log in a PM-1 well is 2.16%, which means it has excellent quality. The prediction of TOC log in a PM-2 well is worth 2.68%, which means it has excellent quality. The correlation value between the TOC log and the TOC core of the PM-1 well is 0.67, which means the correlation is strong. In PM-2 well, the correlation between the TOC log and TOC core is 0.92, which means that the correlation is robust.